2018
DOI: 10.1371/journal.pone.0191590
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of small pulmonary lesions by transbronchial lung biopsy with radial endobronchial ultrasound and virtual bronchoscopic navigation versus CT-guided transthoracic needle biopsy: A systematic review and meta-analysis

Abstract: BackgroundAdvances in bronchoscopy and CT-guided lung biopsy have improved the evaluation of small pulmonary lesions (PLs), leading to an increase in preoperative histological diagnosis.We aimed to evaluate the efficacy and safety of transbronchial lung biopsy using radial endobronchial ultrasound and virtual bronchoscopic navigation (TBLB-rEBUS&VBN) and CT-guided transthoracic needle biopsy (CT-TNB) for tissue diagnosis of small PLs.MethodsA systematic search was performed in five electronic databases, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 56 publications
7
66
0
2
Order By: Relevance
“…This represents a significant improvement compared to CT-guided lung biopsies. 19 The diagnostic yield, however, is lower for lesions smaller than 2 cm. 20 Chen et al clearly demonstrated an increase in yield with each centimeter increase in size of the peripheral lung lesion.…”
Section: Radial Endobronchial Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents a significant improvement compared to CT-guided lung biopsies. 19 The diagnostic yield, however, is lower for lesions smaller than 2 cm. 20 Chen et al clearly demonstrated an increase in yield with each centimeter increase in size of the peripheral lung lesion.…”
Section: Radial Endobronchial Ultrasoundmentioning
confidence: 99%
“…26 The diagnostic yield remains inferior to the percutaneous approach. 19 Virtual Bronchoscopy VB is a noninvasive modality designed to assist with navigation to peripheral pulmonary nodules with flexible bronchoscopy. A three-dimensional (3D) reconstruction of the tracheobronchial tree from noncontrast high-resolution CT images of the chest simulates the view a bronchoscopist has during the procedure.…”
Section: Radial Endobronchial Ultrasoundmentioning
confidence: 99%
“…The complication rates were lower (0% to 7.4%) than CT-guided TTNB [ 56 - 58 ]. Pneumothorax occurred in 1.0% of the patients [ 59 ], and bleeding, infection, and breaking of radial probes can occur in some cases [ 58 ].…”
Section: Endobronchial Ultrasound and A Guide Sheathmentioning
confidence: 99%
“…Other robotic systems [18], [19], [20], [21], [22], including recently released commercial lung biopsy systems [23], [24], offer a bronchoscopic approach via intraluminal steerable needles [25], [26]. However, they have low diagnostic yield in peripheral lungs and for lesions smaller than 20mm [27], [28], [29], [30].…”
Section: Related Workmentioning
confidence: 99%